Origin of zero thermal expansion in an average cubic structure in Pb-free relaxor ferroelectrics - Tripathi A.; Pandey A.; Alonso J.A.; Erasmus R.; Fernandez-Diaz M.T.; Tripathi S. (My University, 2025)
This study presents “K0.5Na0.5NbO3-based” Pb-free smart material 0.80(K0.5Na0.5NbO3)-0.20(Ba0.9Sr0.1TiO3) (KBST20) as exhibiting zero thermal expansion (ZTE) at low temperatures ( T ≤ 100 K) with long-range cubic symmetry stable over a wide temperature range (9 K ≤ T ≤ 500 K). The linear coefficient of the thermal expansion (αl) obtained from temperature-dependent neutron diffraction data is in the range of 0.255-5.75 × 10−6 K-1 (9-500 K), which is rarely observed for Pb-free materials possessing long-range cubic symmetry. The temperature-dependent dielectric data of KBST20 exhibits a strong relaxational behavior with high frequency dispersion ( Δ T ≈ 27 K), suggesting the presence of polar phased regions known as polar nano regions. The ZTE has been attributed to enhanced correlations among PNRs exhibiting ferroelectrostriction. Furthermore, temperature-dependent Raman scattering data reveal polar monoclinic distortion at short ranges rather than cubic symmetry at long ranges. In addition, the intensity of Raman modes increases with the decrease in temperature, suggesting enhancement of the polar phase at low temperatures, which consequently leads to zero thermal expansion in KBST20. © 2024 Author(s).